Automated analysis of human family relationship using facial features - Mohammad Ghahramani (2013)
There has been increasing interest on the use of video surveillance to analyze human biometrics, especially in places where the chance of occurring crime is high, such as in large cities. As an example, 2185 children are being reported missing daily in the United States. It has been rarely looked into belonging a person to the same family as a soft biometric modal. We term the ability to verify query images as family members “family (kinship) verification.” Several studies have been conducted on family photo albuming, but the problem of family verification has not yet been directly addressed and analyzed. The lack of comprehensive published family datasets is evidence that the matter has received very little attention to date. This thesis focuses on providing solutions for challenges of family verification as a recent application of computer vision. We propose frameworks to recognize members of the same family based on the facts and psychological studies on family members’ resemblance to each other. We also investigate the demanding case of missing/unknown member verification as a critical real-life application that will benefit from this research.